2016
DOI: 10.1016/j.jpainsymman.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Topics Discussed During a Conversation Card Game About Death and Dying: A Content Analysis

Abstract: Topics discussed during a nonfacilitated end-of-life conversation game are substantive and address important issues for advance care planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The present study used 20 of the questions that were found effective at eliciting meaningful, clinically relevant discussions. 32 An initial coin toss, whose outcome is not revealed until the end of the game, determines whether the player with the most or the least game chips wins. Games were stopped after 2 hours or when participants finished discussing all 20 questions (whichever came first).…”
Section: Methodsmentioning
confidence: 99%
“…The present study used 20 of the questions that were found effective at eliciting meaningful, clinically relevant discussions. 32 An initial coin toss, whose outcome is not revealed until the end of the game, determines whether the player with the most or the least game chips wins. Games were stopped after 2 hours or when participants finished discussing all 20 questions (whichever came first).…”
Section: Methodsmentioning
confidence: 99%
“…18,24e28 We have previously shown that an end-of-life conversation game ''Hello'' (previously named ''My Gift of Grace'') results in satisfying, realistic, and clinically meaningful conversations. 29,30 Additionally, 70% of participants (with unknown health status) engaged in subsequent ACP behaviors after playing the game. 31 The game has been used successfully in several research settings, including populations of participants with unknown health status in both PA and KY, 29e31 South Asian Indians living in Texas, 32 and chaplainsin-training.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many diverse factors affecting EoL decision-making, such as culture and ethnicity (Duffy et al, 2006;Barnato et al, 2009;Wicher and Meeker, 2012), spiritual beliefs (Shah et al, 2008;Wicher and Meeker, 2012;Delgado-Guay et al, 2016), sexual orientation (Harding et al, 2012;Elk, 2015) and personality (Lattie et al, 2016) and sometimes there is discordance between an individual's values and their stated preferences for EoL care (Heyland et al, 2016). Nevertheless, despite these variances, research into EoL priorities of the general population reveals a number of common priorities, such as: physical comfort and freedom f r o m p a i n ; t h e p r e s e n c e o f f a m i l y a n d strengthening of family relationships; peaceful acceptance of EoL and spiritual concerns being met; relieving stress or burden on the family; avoiding a prolonged period of dying; and achieving a sense of control at a time of great uncertainty (Singer et al, 1999;Heyland et al, 2006;Bausewein et al, 2013;Khan et al, 2013;Van Scoy et al, 2016).…”
Section: End-of-life Priorities and Preferences Within The General (Hmentioning
confidence: 99%